Smarandache zero divisors, power joined elements and triple identity rings. - Hummadi, Parween Ali; Ali, Kurdistan Muhammad (Sulaimani Journal for Pure and Applied Sciences, 2016)
In this paper, we study Smarandache zero divisors, in Zn and the group ring Z2 G, for a cyclic group G of order 2n, we also study power joined elements and triple identity rings.
Keywords: Szero divisors,power joinedelements andTI rings